Hobson y el origen del sistema económico global: Multicultural Origins of the Global Economy. Beyond the Western-Centric Frontier - Olea Contreras, Victor Manuel (México y la Cuenca del Pacífico, 2023)
Reseña del libro: Multicultural Origins of the Global Economy: Beyond the Western-Centric Frontier